Experimental analysis of two-layered dissimilar metals by roll bonding. (16th February 2018) - Zhao, Guanghui; Li, Yugui; Li, Juan; Huang, Qingxue; Ma, Lifeng
Abstract: Rolling reduction and base layers thickness have important implications for rolling compounding. A two-layered 304 stainless steel/Q345R low alloyed steel was roll bonded. The roll bonding was performed at the three thickness reductions of 25%, 40% and 55% with base layers of various thicknesses (Q345R). The microstructures of the composite were investigated by the ultra-deep microscope (OM) and scanning electron microscope (SEM) and Transmission electron microscope (TEM). Simultaneously, the mechanical properties of the composite were experimentally measured and the tensile fracture surfaces were observed by SEM. The interfaces were successfully bonded without any cracking or voids, which indicated a good fabrication of the 304/Q345R composite. The rolling reduction rate and thinning increase of the substrate contributed to the bonding effects appearance of the roll bonded sheet. The Cr and Ni enriched diffusion layer was formed by the interface elements diffusion. The Cr and Ni diffusion led to the formation of ∼10 μ m wide Cr and Ni layers on the carbon steel side.